2015
DOI: 10.3989/scimar.04147.07a
|View full text |Cite
|
Sign up to set email alerts
|

Pasiphaeid shrimps in the western Mediterranean: geographical variability in distribution and population patterns

Abstract: This work aimed to analyse the main characteristics of the bathymetric and geographic distribution, population size structure and size at maturity of the continental slope caridean shrimps Pasiphaea sivado and Pasiphaea multidentata in the western Mediterranean, as well as to try to relate the patterns obtained with geomorphologic and hydrographic characteristics. The study area encompassed the Mediterranean coast of the Iberian Peninsula. In both species, marked differences in depth distribution, density, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The size at which differences in sex ratio become significant has also been suggested to be an indirect indicator of the size at puberty moult and/or maturity size/age of the species (Abelló et al 1990). In the present study, the precise size at which males outnumbered females progressively decreased from the Alboran Sea to the Alacant area and the Catalan Sea, corroborating the patterns of size structure and size at maturity observed in this area (Simão et al 2015) and implying the occurrence of environmental and ecological processes affecting growth rates.…”
Section: Size Dimorphism and Sex Ratiosupporting
confidence: 67%
See 3 more Smart Citations
“…The size at which differences in sex ratio become significant has also been suggested to be an indirect indicator of the size at puberty moult and/or maturity size/age of the species (Abelló et al 1990). In the present study, the precise size at which males outnumbered females progressively decreased from the Alboran Sea to the Alacant area and the Catalan Sea, corroborating the patterns of size structure and size at maturity observed in this area (Simão et al 2015) and implying the occurrence of environmental and ecological processes affecting growth rates.…”
Section: Size Dimorphism and Sex Ratiosupporting
confidence: 67%
“…In the Catalan Sea, the absence of gender segregation by depth was also reported by Company et al (2001) throughout the year, and could be related to the gregarious behaviour of macroplankton/micronekton organisms (McManus and Woodson 2012). During the daytime, P. sivado inhabits the epi-/suprabenthic environment over the upper and medium slope, with high densities recorded when sampled by demersal trawl nets during fishery research surveys (Cartes et al 2007, García-Rodríguez et al 2011, Simão et al 2015, while during the night the species has been reported to migrate several hundred metres up the water column to waters near the surface to feed on plankton (Froglia and Giannini 1982, Cartes 1993, Simão et al 2014.…”
Section: Size Dimorphism and Sex Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…It is necessary to listen to the masters and bring them to teach, without interfering with their personal way of teaching. What is expected is to seek "[…] an identity that is not the one imposed by Europeans, even if their influences remain" in our bodies and minds (Simão;Sampaio, 2018, p. 674).…”
Section: Jogo Bonito Esse Jogo é De Angola (Beautiful Game This Game ...mentioning
confidence: 99%